Fatty Infiltration of Cervical Spine Extensor Musculature: Is there a Relationship With Cervical Sagittal Balance?. Issue 10 (December 2018) - Passias, Peter G.; Segreto, Frank A.; Bortz, Cole A.; Horn, Samantha R.; Frangella, Nicholas J.; Diebo, Bassel G.; Hockley, Aaron; Wang, Charles; Shepard, Nicholas; Lafage, Renaud; Lafage, Virginie
Abstract : Study Design: This is a retrospective review of a single surgeon cervical deformity (CD) database. Objective: Quantitatively describe the cervical extensor musculature in a CD population, and delineate associations between posterior musculature atrophy and progressive sagittal deformity. Summary of Background Data: While fatty infiltration (FI; ie, posterior musculature atrophy) of lumbar extensor musculature has been associated with pain and deformity, little is known of the relationship between FI, CD, cervical sagittal alignment, and functionality. Methods: CD patients [TS-CL>20 degrees, C2–C7 Cobb>10 degrees, CL>10 degrees, cervical sagittal vertical axis (cSVA)>4 cm, or chin-brow vertical angle>25 degrees] 18 years old and above, undergoing spinal fusion, with baseline T2-weighted magnetic resonance images were included. FI was assessed using dedicated imaging software at each intervertebral level from C2–C7. FI was gauged as a ratio of fat-free muscle cross-sectional area over total muscle cross-sectional area, with lower values indicating increasing FI. Influence of BL C2–C7 FI on patient-reported outcome measures (PROMs) and alignment was investigated. Multiple linear regression analysis (covariates: age, sex, body mass index, C2–C7 FI ratio) determined predictors of postoperative sagittal alignment and PROMs. Results: Thirty-eight patients were included (age: 56.6, sex: 73.7% female, body mass index: 30.1, Charlson Comorbidity Index 0.61). BL deformity presentation: TS–CL 27.4 degrees, CL 2.1 degrees, cSVA: 27.2 mm. Mean baseline C2–C7 FI ratio was 0.65±0.11. Worsening FI was associated with malaligned baseline cSVA ( r s =0.389, P =0.019), T1SS ( r s =0.340, P =0.062), and impaired gait ( r s =0.358, P =0.078). FI was not associated with BL PROMs ( P >0.05). Following surgical intervention, regression models determined BL C2–C7 FI ratio as the strongest predictor of 1-year postoperative cSVA (β=−0.482, P =0.007, R 2 =0.317). No associations between BL FI and postoperative PROMS or alignment parameters were observed ( P >0.05). Conclusions: Patients with significant CD demonstrate alterations in the posterior extensor musculature of the cervical spine. Atrophic changes with FI of these muscle groups is associated with worsening CD and is an important predictor of postoperative sagittal alignment. Level of Evidence: Level III.